Predictive factors of incidental prostate cancer in patients undergoing surgery for presumed benign prostatic hyperplasia: an updated systematic review and meta-analysis - Wang, Yang; Li, Xiancheng; Yang, Hua; Yin, Chaoshan; Wu, Yameng; Chen, Xiaoke (Frontiers in Oncology, 2025)
PurposeWe aimed to identify the clinical predictors of incidental prostate cancer (IPCa) after surgery for presumed benign prostatic hyperplasia (BPH).MethodsThe literature was comprehensively searched using PubMed, Web of Science, Embase, and Cochrane databases in December 2024. We used pooled standardized mean difference (SMD) and odds ratio (OR) to describe the correlation between relevant risk factors and IPCa.ResultsTwenty-one studies included 10,842 patients that were available for further analysis. After BPH surgery, 957 patients were histopathologically diagnosed with IPCa. The IPCa rate was 8.83%. Most importantly, our results identified that IPCa was significantly associated with age (pooled SMD = 0.36, P < 0.001), body mass index (BMI) (pooled SMD = 0.23, P < 0.001), preoperative prostate-specific antigen (pre-PSA) (pooled SMD = 0.43, P < 0.001), preoperative prostate-specific antigen density (pre-PSAD) (pooled SMD = 0.62, P = 0.028), resected prostate weight (pooled SMD = -0.22, P < 0.001), preoperative treatment with 5-alpha reductase inhibitors (5αRIs) (yes/no) (pooled OR = 0.60, P < 0.001), family history (yes/no) (pooled OR = 3.81, P = 0.029), digital rectal examination (DRE) findings (abnormal/normal) (pooled OR = 5.15, P < 0.001), and transrectal ultrasonography (TRUS) findings (abnormal/normal) (pooled OR = 2.92, P < 0.001). Additionally, sensitivity and subgroup analyses indicated that our findings were reliable and robust. However, we found no significant associations between IPCa and prostate volume, preoperative negative prostate biopsy, smoking history, history of hypertension, history of diabetes, history of dyslipidemia, and abnormal magnetic resonance imaging findings (all P > 0.05).ConclusionsAge, BMI, pre-PSA, pre-PSAD, resected prostate weight, preoperative treatment with 5αRIs, family history, abnormal DRE findings, and abnormal TRUS findings are independent factors predicting IPCa following BPH surgery. Before BPH surgery, factors such as age, BMI, pre-PSA, and pre-PSAD should be considered to assess the risk of IPCa. For high-risk patients, more detailed imaging and needle biopsy are recommended before surgery to avoid missed diagnosis. In the future, more large-scale and well-designed studies are needed to validate our results further.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42025631346.